2017
DOI: 10.3390/rs9100991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Expansion on Forest Loss and Fragmentation in Six Megaregions, China

Abstract: Abstract:Urban expansion has significant effects on forest loss and fragmentation. Previous studies mostly focused on how the amount of developed land affected forest loss and fragmentation, but neglected the impacts of its spatial pattern. This paper examines the effects of both the amount and spatial pattern of urban expansion on forest loss and fragmentation. We conducted a comparison study in the six largest urban megaregions in China-Beijing-Tianjin-Hebei (BTH), Yangtze River Delta (YRD), Pearl River Delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…There may exist a time-lag effect of fires, meaning forest loss likely occurs after fire burning over a longer period (e.g., years after fire burning). Second, studies suggest that other causes of forest loss should be considered (van Lierop et al 2015), such as urban expansion (Zhou et al 2017), timber harvesting (Wu et al 2019), and ice storm damage (Yang et al 2008). For example, urban expansion was suggested as a major factor causing forest loss in six mega regions of southern China (Zhou et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may exist a time-lag effect of fires, meaning forest loss likely occurs after fire burning over a longer period (e.g., years after fire burning). Second, studies suggest that other causes of forest loss should be considered (van Lierop et al 2015), such as urban expansion (Zhou et al 2017), timber harvesting (Wu et al 2019), and ice storm damage (Yang et al 2008). For example, urban expansion was suggested as a major factor causing forest loss in six mega regions of southern China (Zhou et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, on 6 May 1987, a fire in the boreal forests of northeastern China burned ~ 1.3 × 10 6 ha and significantly affected forest resources and the environment (Xiao et al 1988;Cahoon et al 1994). Although the patterns and drivers (e.g., urban expansion) of forest loss have been examined in some regions of China (Jia et al 2015;Zhai et al 2017;Zhou et al 2017), an understanding of the effects of fires on forest loss on a national scale for China is still lacking. Filling this gap in our knowledge will increase the accuracy of predictions of future trends in forest change (loss or gain) in China.…”
Section: Introductionmentioning
confidence: 99%
“…Aerial and satellite-based remote sensing has been commonly used for monitoring urban forest cover change and understanding urban forest cover and fragmentation patterns [17,18]. Individual year or perennial data that employ moderate to coarse resolution imagery have been frequently investigated to track forest change and monitor fragmentation [19][20][21][22]. Multi-temporal high resolution satellite imagery and light detection and ranging (LiDAR) data also play an important role in capturing accurate and detailed spatial patterns of fragmentation of urban forest cover, although the application of these datasets are limited in their spatial and temporal coverage [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Fragmentation metrics and analysis models have been widely utilized in existing studies to monitor landscape fragmentation patterns from local to global scales [19,20,[40][41][42][43]. Zhou et al [22] explored the statistical relationships between urban expansion and forest loss and landscape metrics-based fragmentation using correlation analysis. It has been found that urban expansion was a major driver of forest loss, and its cover has impacts on forest fragmentation; however, the relationships between the spatiotemporal pattern of forest loss and fragmentation were rarely examined [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation